2009
DOI: 10.3402/tellusb.v61i1.16832
|View full text |Cite
|
Sign up to set email alerts
|

EARLINET observations of the 14–22-May long-range dust transport event during SAMUM 2006: validation of results from dust transport modelling

Abstract: A B S T R A C TWe observed a long-range transport event of mineral dust from North Africa to South Europe during the Saharan Mineral Dust Experiment (SAMUM) 2006. Geometrical and optical properties of that dust plume were determined with Sun photometer of the Aerosol Robotic Network (AERONET) and Raman lidar near the North African source region, and with Sun photometers of AERONET and lidars of the European Aerosol Research Lidar Network (EARLINET) in the far field in Europe. Extinction-to-backscatter ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 11 publications
3
25
0
1
Order By: Relevance
“…A mean value of 1.2±0.6 is obtained for the Angstrom exponent at 532/355 nm. The observed values of lidar ratio at 355 nm and 532 nm are in perfect agreement with the 3-year study on Saharan dust intrusions over Potenza (Mona et al, 2006) and with values of 55-60 sr at 532 nm observed at CNR-IMAA during a long-range dust transport event (Müller et al, 2009). Moreover, during the same long-range dust transport event, 532/355 nm Angstrom exponent values of 0.5-0.8 have been observed at CNR-IMAA (Müller et al, 2009).…”
Section: An Example Of Comparisonsupporting
confidence: 73%
See 2 more Smart Citations
“…A mean value of 1.2±0.6 is obtained for the Angstrom exponent at 532/355 nm. The observed values of lidar ratio at 355 nm and 532 nm are in perfect agreement with the 3-year study on Saharan dust intrusions over Potenza (Mona et al, 2006) and with values of 55-60 sr at 532 nm observed at CNR-IMAA during a long-range dust transport event (Müller et al, 2009). Moreover, during the same long-range dust transport event, 532/355 nm Angstrom exponent values of 0.5-0.8 have been observed at CNR-IMAA (Müller et al, 2009).…”
Section: An Example Of Comparisonsupporting
confidence: 73%
“…The observed values of lidar ratio at 355 nm and 532 nm are in perfect agreement with the 3-year study on Saharan dust intrusions over Potenza (Mona et al, 2006) and with values of 55-60 sr at 532 nm observed at CNR-IMAA during a long-range dust transport event (Müller et al, 2009). Moreover, during the same long-range dust transport event, 532/355 nm Angstrom exponent values of 0.5-0.8 have been observed at CNR-IMAA (Müller et al, 2009). This is in good agreement with the hypothesis that the layer observed on 13 August 2006 is related to dust intrusion: the 2 observed values are in agreement within the errors and moreover on 13 August 2006 the Angstrom exponent increases with the altitudes with a value in the middle of the layer of about 0.9.…”
Section: An Example Of Comparisonsupporting
confidence: 73%
See 1 more Smart Citation
“…The passive microwave radiometer performs measurements of the sky brightness temperature with a radiometric resolution between 0.3 and 0.4 K root mean square error at 1 s integration time (Navas-Guzman et al, 2014). The radiometer uses direct detection receivers within two bands: 22Á31 and 51Á58 GHz.…”
Section: Passive Remote Sensing Instrumentationmentioning
confidence: 99%
“…The data from both campaigns have already been used for extensive model evaluation (e.g. Tegen et al, 2006;Bouet et al, 2007;Todd et al, 2007Todd et al, , 2008aHaustein et al, 2009;Heinold et al, 2009;Müller et al, 2009;Otto et al, 2009Otto et al, , 2011. The first phase of SAMUM-1 took place in May/June 2006 at three sites in Morocco accompanied by overflights of two research aircraft as integral part of the campaign.…”
Section: Introductionmentioning
confidence: 99%